2007
DOI: 10.1592/phco.27.11.1498
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gatifloxacin and Levofloxacin on Rates of Hypoglycemia and Hyperglycemia Among Elderly Hospitalized Patients

Abstract: Higher rates of both hypoglycemia and hyperglycemia were noted among elderly hospitalized patients who received gatifloxacin compared with those receiving levofloxacin, irrespective of dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…One contributing factor may be overexposure (eg, failure to adjust the dose in patients with renal insufficiency) [32]. The results of our study and of others [12,15,16,20,21], as well as this potentially common mechanism for hypoglycemia, suggest the need for caution when using certain fluoroquinolones, because the odds of hypo-and hyperglycemia appear to vary among the agents [33]. This is not unusual; differences in risk have been reported for other adverse effects with this class of antibiotics [34].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…One contributing factor may be overexposure (eg, failure to adjust the dose in patients with renal insufficiency) [32]. The results of our study and of others [12,15,16,20,21], as well as this potentially common mechanism for hypoglycemia, suggest the need for caution when using certain fluoroquinolones, because the odds of hypo-and hyperglycemia appear to vary among the agents [33]. This is not unusual; differences in risk have been reported for other adverse effects with this class of antibiotics [34].…”
Section: Discussionsupporting
confidence: 52%
“…However, gatifloxacin-which had been used in the treatment of a variety of infections, including those involving the skin and the respiratory and genitourinary tracts [1,2]-was withdrawn from the market because of concerns about severe glucose disturbances. Although hypoglycemia and hyperglycemia were reported only rarely during clinical trials with gatifloxacin, severe dysglycemic events, typically in elderly patients and in patients with diabetes, were re-ported during the postmarketing period [3] and published in the medical literature [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
mentioning
confidence: 99%
“…Similarly, the widely used fluoroquinolone antibiotics that also block the K v 11.1 1 have been associated with hypoglycemia both in patients with and without diabetes mellitus, and with fatal hypoglycemia, as well, when used together with sulfonylurea. 1,38,39 Indeed, several widely used pharmaceutical agents are known to block the Kv11.1 channel, 1,27 and may, therefore, on the background of the present observations, also be suspected to increase the risk of reactive hypoglycemia.…”
Section: Discussionmentioning
confidence: 63%
“…Specifically, the RR of hypoglycemia with gatifloxacin was more than twofold higher than with levofloxacin, the molecule more frequently captured among case reports collected [9,19,25,[74][75][76]80]. In keeping with this, both descriptive and etiological surveys showed that levofloxacin users were more at risk of dysglycemia than those exposed to ciprofloxacin [9,19,25,[56][57][58][59][60][61][62][63][64][74][75][76]. Moreover, almost all case reports and series confirmed that predisposing factors, such as diabetes, kidney failure and use of antidiabetics (e.g., glyburide) were able to increase the risk of blood glucose disorders within a short time of onset.…”
Section: Discussionmentioning
confidence: 99%